Optimation of In vitro Lateral Shoots Multiplication of Papaya (Carica papaya L.) “Callina” with BAP and NAA - Efendi, Darda; Putra, Mirza R (Department of Agronomy and Horticulture, IPB University, 2017)
Papaya is a popular fruit and is grown commercially in many subtropical and tropical countries. Papayas are generally grown from seeds; therefore the offsprings are not true-to-type and could come in three sexes, female, male, and hermaphrodite. Clonal propagation is required to obtain to grow true-to-type hermaphrodite papayas. In this research, we developed an in vitro protocol for shoot multiplication from lateral shoots from in vitro germinated papaya seedlings. The in vitro propagated plant materials could potentially be used as a source of papaya micro cuttings, or as scion for papaya grafting. The experiment was set up as a factorial experiment with NAA at 0, 0.1 and 0.5 mg.L-1, and BAP at 0, 0.1, 0.5, and 1.0 mg.L-1 in a completely randomized block design. BAP interacted with NAA in affecting the shoot production per explant. The optimum BAP and NAA concentration to produce lateral shoots was 0.54 mg. L-1 and 0.1 mg.L-1, respectively. Media without NAA reduced the number of lateral shoots and number of leaf per explant at any BAP concentration.Keywords: hermaphrodite, seeds, true to type, clonal propagation, micro cuttings.